The minority of three-game: An experimental and theoretical analysis - Thorsten Chmura; Werner Güth; Thomas Pitz; Anthony Ziegelmeyer (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
We report experimental and theoretical results on the minority of three-game where three players have to choose one of two alternatives independently and the most rewarding alternative is the one chosen by a single player. This coordination game has many asymmetric equilibria in pure strategies that are non strict and payoff-asymmetric, and a unique symmetric mixed strategy equilibrium in which each player's behavior is based on the toss of a fair coin. We show that such a straightforward behavior is predicted by Harsanyi and Selten's (1988) equilibrium selection theory as well as alternative solution concepts like impulse balance equilibrium and sampling equilibrium. Our results indicate that participants rely on various decision rules, and that only a quarter of them decide according to the toss of a fair coin. Reinforcement learning is the most successful decision rule as it describes best the behavior of about a third of our participants.
Keywords: C72; C91; D83; 330; coordination; minority game; mixed strategy; learning models; experiments; Nichtkooperatives Spiel; Lernprozess; Test; Theorie